PENGARUH PENGGUNAAN TPS TERHADAP HASIL BELAJAR IPS KELAS V SDN 23 SUNGAI RAYA - Dewi, Fiara Amelia; Marli, Suhardi; Uliyanti, Endang (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Abstract The aim of this research is to fird of out the influence of using TPS toward the outcome of IPS learning on class V SDN 23 Sungai Raya Kubu Raya. The method used is experimental study. With pre experimental design, with kind of experimental one grup pretest-posttest design. The technique of data collecting used is test in from of multiple choice which consist of 50 items. The result of the research is the average score of pretest 54,33, while the average score of post-test 67,20, t-test price tcount compared ttable with dk= 24-1=23 and the significance level (α) 0,01 the price of ttable=2,81. Tcount ≥ ttable or 3,71  ≥ 2,81 means significant, it conclude that Ho is rejected, whereas Ha is accepted. It can be conclude that there is an influence of  using TPS type of cooperative model toward the outcome of IPS learning on class V SDN 23 Sungai Raya Kubu Raya, that is about 0,78 with the medium category. Keywords: Influence, TPS, Learning Outcomes